Methylene Blue in Ventilator-Induced Lung Injury after Pneumonectomy: an Experimental Study - Ye. V Suborov; V. V. Kuzkov; M. Sobkhez; M. Yu. Kirov; L. J. Bjertnaes (Общая реаниматология)
Objective: to study the expediency and efficiency of using methylene blue (MB) on a model of pneumectomy (PE) and subsequent ventilator-induced lung injury (VILI) in sheep. Materials and methods. The study was conducted at the Research Laboratory of University of Tromse. The experiment included 23 sheep weighing 41.0±4.9 kg. Thoracotomy and right-sided pneumonectomy were performed in the animals under general anesthesia and controlled artificial ventilation. After measurement of the parameters of systemic hemodynamics and extravascular water of the lung (EVWL), the animals were divided into 3 groups: 1) a control group (CG, n=7) with a tidal volume (TV) of 6 ml/kg and an end-expiratory positive pressure (PEEP) of 2 cm H2O; 2) a VILI group (n=9) with a TV of 12 ml/kg and a PEEP of 0 cm H2O; 3) a group of MB (n=7) that was given in parallel with a damaging ventilation mode. The thermodilution technique (using a Cold Z-021 monitor, (Pulsion, Germany)) was employed to measure volumetric parameters and EVWL. The parameters of pulmonary hemodynamics, respiratory mechanics, and blood gas composition were recorded. Results: After its reduction at PE, EVWL index increased during damaging ventilation in the VILI and MB groups. In addition, there was an increase in pulmonary artery wedge pressure after PE in the MB and VILI groups. In the latter group, arterial hypoxemia was observed at the end of the experiment. Along with this, after PE pulmonary compliance decreased and airway pressure elevated in the VILI and MB groups. Conclusion: In the presented model of VILI, MB does not prevent the development of postp-neumectomic edema of the lung. Key words: thermochromodilution, acute lung injury, pneumectomy, ventilator-induced lung injury, postpneumectomic edema of the lung, methylene blue.